Persepsi dan Kepuasan Mahasiswa Terhadap Program Magang di Industri Pariwisata Luar Negeri (Studi Kasus Mahasiswa Perguruan Tinggi Pariwisata di Jakarta) - Sembiring, Vienna Artina; Rahayu, Nurti; Tarigan, Emenina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
To improve the quality of tourism human resources with global quality, tourism universities hold an internship program in the tourism industry abroad. This study aims to reveal (1) students' perceptions of the internship program in the tourism industry abroad; (2) student satisfaction with the internship program in the tourism industry abroad; and (3) the influence of perceptions on student satisfaction with the internship program in the tourism industry abroad. The study population was all students from higher education in tourism in Jakarta and its surroundings who had completed an internship program in the tourism industry abroad. Samples were taken using convenient sampling using valid and reliable instruments with 4 Likert scales with Google Form media (N = 100). The results of the analysis with SPSS 22 showed that students' perceptions were good, while students was categorized as satisfied with the internship program. The result of the correlation test confirmed the significant relationship between perception variables and satisfaction on the program. The regression analysis showed that students’ perception significantly affected their internship satisfaction. The results of this study serve as a valuable input for the campus, industry, and policy makers to improve the design of the internship program curriculum. Keywords: Tourism Industry; Satisfaction; Internship; Perception